1993
DOI: 10.1002/cyto.990140307
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric screening of blood samples for malaria parasites

Abstract: method for the detection and estimation of malaria parasites in blood samples using flow cytometry is presented. In a single-step procedure 50 ~1 of blood sample was collected in 1 ml of lysis solution containing formaldehyde, causing red blood cells to lyse while parasites and white blood cells are preserved. Thus prepared, samples could be transported and remained stored in lysis solution until flow cytometric analysis was performed. The cells were stained for DNA with the fluorescent dye Hoechst 33258 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…Experimental malaria-cytometry studies have found a detection threshold of 50 parasites/μL. 30 Furthermore, in a study using a Sysmex SIF flow cytometer, the authors were able to differentiate P. falciparum parasite stages based on fluorescence patterns, 31 providing evidence for the potential for improving malaria detection with commercial flow cytometers, including the XE-2100. Our findings, specially the N-OD2 models, suggest that the XE-2100 could become an accurate tool for malaria diagnosis, allowing for a timely microscopic blood evaluation of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental malaria-cytometry studies have found a detection threshold of 50 parasites/μL. 30 Furthermore, in a study using a Sysmex SIF flow cytometer, the authors were able to differentiate P. falciparum parasite stages based on fluorescence patterns, 31 providing evidence for the potential for improving malaria detection with commercial flow cytometers, including the XE-2100. Our findings, specially the N-OD2 models, suggest that the XE-2100 could become an accurate tool for malaria diagnosis, allowing for a timely microscopic blood evaluation of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry has been successfully used to analyze parasite development by determining the amount of DNA synthesized using DNA-specific dyes (37). By simultaneously staining for erythrocyte surface CD59 and parasite DNA, we are able to assess intraerythrocytic infection by the malaria parasite.…”
Section: Movement Of Erythrocyte Raft Proteins and Lipids Into A Malamentioning
confidence: 99%
“…30 Other diagnostic methods include automated detection of malaria pigment 38 and flow cytometry. 39 Serologic tests have no role in the diagnosis of acute malaria.…”
Section: Diagnosismentioning
confidence: 99%